2021
DOI: 10.1021/acs.iecr.1c02636
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Coating of Needle-like NiCo2O4 Magnetic Nanoparticles on Lightweight Reticulated Vitreous Carbon Foam toward Achieving Improved Electromagnetic Wave Absorption

Abstract: To improve electromagnetic (EM) wave attenuation and its absorption properties, herein, for the first time, we grow needle-like magnetic NiCo2O4 nanoparticles in situ on lightweight open cell reticulated vitreous carbon (RVC) foam by the hydrothermal method, leading to hierarchically nanostructured foam. The foam was synthesized by the carbonization of flexible polyurethane foam followed by acid treatment. The coating structure, stability, and performance were systematically investigated by various complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…[26] The bands at 1509 cm À 1 , 1376 cm À 1 , and 3339 cm À 1 indicate the presence of HÀ OÀ H bending vibration mode. [27] The two bands at 747 cm À 1 and 827 cm À 1 can be attributed to metal-oxygen of CoÀ O and NiÀ O stretching vibrations and the formation of spinel NiCo 2 O 4 structure. [28] Significant blue-shift of NiÀ O indicates a strong bond, perhaps a hydrogen bonding, between the CF and NiCo 2 O 4 particles, wherein the carbonyl group of CF and the NiÀ O groups of NiCo 2 O 4 are involved.…”
Section: Phase Analysis Of Nico 2 O 4 /Cf Compositesmentioning
confidence: 99%
“…[26] The bands at 1509 cm À 1 , 1376 cm À 1 , and 3339 cm À 1 indicate the presence of HÀ OÀ H bending vibration mode. [27] The two bands at 747 cm À 1 and 827 cm À 1 can be attributed to metal-oxygen of CoÀ O and NiÀ O stretching vibrations and the formation of spinel NiCo 2 O 4 structure. [28] Significant blue-shift of NiÀ O indicates a strong bond, perhaps a hydrogen bonding, between the CF and NiCo 2 O 4 particles, wherein the carbonyl group of CF and the NiÀ O groups of NiCo 2 O 4 are involved.…”
Section: Phase Analysis Of Nico 2 O 4 /Cf Compositesmentioning
confidence: 99%
“…Therefore, we can rule out a contribution from magnetic losses. Dielectric loss is related to interfacial polarization, defect-induced polarization, dipole/molecular polarization, electronic polarization, ionic polarization, and atomic polarization 65,66 . Ionic, atomic, and electronic polarization are not present in the 2-18 GHz range.…”
Section: Samplementioning
confidence: 99%
“…By increasing ε", the alternate current (AC) conductive increases further enhancing conductive loss. The ionic and electronic polarization occurs in the ultraviolet or infrared region 65,66 . The dielectric loss behavior can be explained by the Debye theory.…”
Section: Samplementioning
confidence: 99%
“…The resulting nanoneedle "forest" was found to be strongly bonded to the carbon substrate. 28 A strong bond of active material with the substrate is paramount for the long-term electrochemical performance of the electrode. 29 This strategy would effectively provide and utilize the active material's surface area, and more importantly, it is binder-free.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that NiCo 2 O 4 grown on RVC foam significantly improved the EMI shielding and microwave absorption properties of the RVC foam. 28 However, this newly developed material's electrochemical properties and energy storage capability are still unknown.…”
Section: Introductionmentioning
confidence: 99%